2012
DOI: 10.4253/wjge.v4.i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal squamous cell carcinoma - precursor lesions and early diagnosis

Abstract: Squamous cell carcinoma of the esophagus (SCCE) carries a poor prognosis due to late diagnosis. Early detection is highly desirable, since surgical and endoscopic resection offers the only possible cure for esophageal cancer. Population screening should be undertaken in high risk areas, and in low or moderate risk areas for people with risk factors (alcoholics, smokers, mate drinkers, history of head and neck cancer, achalasia and lye stricture of the esophagus). Esophageal balloon cytology is an easy and inex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 73 publications
0
42
0
5
Order By: Relevance
“…The most sensitive tool for the early detection of EC is chromoendoscopy with Lugol's dye [33]. During the 1990s, multiple reports demonstrated that endoscopy provided an easy, inexpensive, and sensitive means of detecting early and late squamous cell neoplasia.…”
Section: Early Ec Detectionmentioning
confidence: 99%
“…The most sensitive tool for the early detection of EC is chromoendoscopy with Lugol's dye [33]. During the 1990s, multiple reports demonstrated that endoscopy provided an easy, inexpensive, and sensitive means of detecting early and late squamous cell neoplasia.…”
Section: Early Ec Detectionmentioning
confidence: 99%
“…However, many patients in the routine screening group had advanced ESCC, with the primary survey identifying tumor invasion of other adjacent structures or regional lymph node metastases (and even distant metastases). The introduction of techniques such as narrow band imaging 15,16 and Lugol dye spray chromoendoscopy 17 or shortening the interval between examinations to 3 months may be helpful in these patients to diagnose earlier ESCC.…”
Section: Commentmentioning
confidence: 99%
“…It was not detected preoperatively, probably due to lack of adequate preparation for endoscopy. Although our series of cases is very limited, it reproduces the well known risk factors for esophageal squamous cell carcinoma 1,3,6 .…”
Section: Outcome Of Superficial Squamous Cell Carcinoma Of the Esophamentioning
confidence: 98%
“…Therefore, the best strategy to improve the chances of long-term survival is the identification of lesions at early stage 5,6 .…”
Section: Introductionmentioning
confidence: 99%